The Threat of Exclusion and Relational Contracting - Martin Brown; Marta Serra-Garcia (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2011)
Relational contracts have been shown to mitigate moral hazard in labor and credit markets. A central assumption in most theoretical and experimental studies is that, upon misbehaving, agents can be excluded from their current source of income and have to resort to less attractive outside options. This threat of exclusion is unrealistic in many environments, and especially in credit and investment contexts. We examine experimentally the emergence and time structure of relational contracts when the threat of exclusion is weakened. We focus on bilateral credit relationships in which strategic default is possible. We compare a weak exclusion treatment in which defaulting borrowers can reinvest borrowed funds, to a strong exclusion treatment in which defaulting borrowers must liquidate borrowed funds. We find that under weak exclusion more relationships break down in early periods and credit relationships are more likely to “start small”.
urn:nbn:de:bvb:19-epub-12287-8
Keywords: C73; G21; O16; F21; F34; 330; Relational contracts; Starting small; Debt enforcement; Kredit; Unvollständiger Vertrag; Kreditrisiko; Schuldrecht; Rechtsdurchsetzung; Theorie